2008
DOI: 10.1016/j.aquaculture.2008.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary phospholipid levels on performance, enzyme activities and fatty acid composition of pikeperch (Sander lucioperca) larvae

Abstract: This study was carried out to evaluate the effects of dietary phospholipid on the development and rearing performance of pikeperch (Sander lucioperca) larvae. From day 10 post-hatching, fish larvae were weaned onto three isoproteic and isolipidic formulated diets with different phospholipid (PL) levels: 1.4 (PL1), 4.7 (PL5) and 9.5% (PL9) of dry matter, as soybean lecithin. Neutral lipid (NL) with inversed gradient was incorporated in diets. Survival, growth and deformities were monitored until day 34 post-hat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
78
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 61 publications
18
78
0
1
Order By: Relevance
“…It was reported that fish larvae utilize dietary phospholipids more efficiently than neutral lipids [19] and have high requirements of phospholipids such as at least 9.5% for pikeperch larvae [20] and 6.95-8.51% for large yellow croaker larvae [21] so in this study, 10% of soy lecithin was supplemented to all experimental diets. The 4.1 kcal/g diet of digestible energy level was closed to those of values in diets for pikeperch larvae [20] and European sea bass larvae [22].…”
Section: Introductionmentioning
confidence: 97%
“…It was reported that fish larvae utilize dietary phospholipids more efficiently than neutral lipids [19] and have high requirements of phospholipids such as at least 9.5% for pikeperch larvae [20] and 6.95-8.51% for large yellow croaker larvae [21] so in this study, 10% of soy lecithin was supplemented to all experimental diets. The 4.1 kcal/g diet of digestible energy level was closed to those of values in diets for pikeperch larvae [20] and European sea bass larvae [22].…”
Section: Introductionmentioning
confidence: 97%
“…Larvae of S. lucioperca had low activities of proteolytic enzymes, high activities of lipolytic enzymes, and medium range activities of carbohydrate splitting enzymes. Thus could indicate the specialization of S. lucioperca larvae on a lipid rich diet which is also established by results obtained in larvae feeding experiments (Hamza et al 2008). The highest activities of proteolytic, lipolytic, and carbohydrate splitting enzymes were observed in C. maraena and T. thymallus which is interpreted in favour of a well-developed digestive system capable of digesting a broad range of nutrients.…”
Section: Discussionmentioning
confidence: 58%
“…Thymallus thymallus, Coregonus sp., Sander lucioperca, and Lota lota. In S. lucioperca larvae differentiation of key digestive enzymes (Cuvier-Peres andKestemont doi: 10.17221/25/2016-CJAS 2001;Hamza et al 2015) and effects of different diets and weaning conditions on selected digestive enzyme activities were investigated (Hamza et al 2007(Hamza et al , 2008. In Coregonus lavaretus larvae enzyme activities in different segments of the intestine were investigated by histochemical methods (Segner et al 1989).…”
mentioning
confidence: 99%
“…(Nagahama, 1994;Nagahama, 1999;Peter e Yu, 1997;Blázquez et al, 1998 Como dito anteriormente os lipídios constituídos pelos ácidos graxos são mobilizados do tecido adiposo dos peixes durante a maturação gonadal e transferidos pelo plasma para o fígado, onde serão reorganizados na vitelogenina (Bromage, 1995). Níveis inadequados de ácidos graxos essenciais em uma dieta podem comprometer a formação de estruturas nas membranas celulares, causando uma maior incidência de deformações nos tecidos das larvas (Hamza et al, 2008). Para um crescimento normal nos peixes, incluindo desenvolvimento e reprodução, são necessários principalmente três tipos de ácidos graxos polinsaturados (PUFA) com longas cadeias de carbonos, são eles, ácidos docosahexanóico (DHA, C22:6n3), ácido eicosapentanóico (EPA, C20:5n3) e ácido araquidônico (AA, C20:4n6) (Sargent et al, 2001).…”
Section: Espécie Modelounclassified
“…Inadequate levels of essential fatty acids in the diet can compromise the cell membrane structure, causing a higher incidence of deformations in larva tissues (Hamza et al, 2008). The physiological roles of fatty acids in reproduction, embryogenesis and larval development have been described for several marine (Fraser et al, 1988;Wiegand 1996;Rainuzzo et al, 1997;Sargent et al, 1999) and freshwater species (Gunasekera et al, 1999;Palácios et al 2007), but little is known in tropical fish species.…”
Section: Introductionmentioning
confidence: 99%